2019
DOI: 10.3892/etm.2019.8318
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA‑214 and galectin‑3 in peripheral blood of patients with chronic heart failure and its clinical significance

Abstract: Expression of microRNA (miR)-214 and galectin-3 (Gal-3) in peripheral blood of patients with chronic heart failure (CHF) and its clinical significance were investigated. A total of 50 cases of CHF patients, diagnosed and treated in Shanghai Xuhui Central Hospital from January 2017 to March 2018, were the study group and 30 healthy subjects who underwent physical examination during the same period were the control group. Concentration of serum Gal-3 was detected by ELISA and the expression of miR-214 in serum w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…In the study by Han et al [ 144 ], the clinical importance was assessed of miR-214 and serum galectin-3 concentration in whole blood of patients with chronic heart failure. A statistically significant increase was noted of both miR-214 expression and galectin-3 serum concentration in the group with chronic heart failure.…”
Section: Ncrnas As the Modulators Of Lgals3 Gene Expression And A New Potential Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Han et al [ 144 ], the clinical importance was assessed of miR-214 and serum galectin-3 concentration in whole blood of patients with chronic heart failure. A statistically significant increase was noted of both miR-214 expression and galectin-3 serum concentration in the group with chronic heart failure.…”
Section: Ncrnas As the Modulators Of Lgals3 Gene Expression And A New Potential Therapeutic Targetmentioning
confidence: 99%
“…A positive correlation was demonstrated between miR-214 expression and serum galectin-3 concentration, what suggested the participation of both factors in the development of chronic heart failure. Galectin-3 exerts an effect promoting the myocardial fibrosis process, while miR-214 can regulate fibroblast proliferation [ 144 ].…”
Section: Ncrnas As the Modulators Of Lgals3 Gene Expression And A New Potential Therapeutic Targetmentioning
confidence: 99%
“…Second, galectin-3 levels correlate with diastolic (Ansari et al, 2018) and systolic dysfunction (Zivlas et al, 2017). Third, following treatment of heart failure, galectin-3 levels were significantly decreased (Han et al, 2020). We found that galectin-3 is significantly increased in cirrhotic rat hearts, and a galectin inhibitor, N-acetyllactosamine, significantly improved cardiac function (Yoon et al, Forthcoming 2022).…”
Section: Other Substancesmentioning
confidence: 67%
“…In addition, one of the studies collected blood from two different locations from the same patients (vein and coronary sinus); 24% of studies used TaqMan assay to measure expression levels of miRNAs; 42% and 29% of studies were conducted in China and Europe between 2010 and 2021, respectively ( Table 1 and online supplementary Table Appendix S1 ). 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Resultsmentioning
confidence: 99%